The differences in virus shedding time between the Delta variant and original SARS-CoV-2 infected patients - Li, Fanglin; Deng, Jiayi; Xie, Canbin; Wang, Guyi; Xu, Min; Wu, Chenfang; Li, Jinxiu; Zhong, Yanjun (Frontiers in Public Health, 2023)
Background The worldwide epidemic of Coronavirus Disease 2019 (COVID-19) has evolved into multiple variants. The Delta variant is known for its ability to spread and replicate, while data are limited about the virus shedding time in patients infected by the Delta variant. Methods 56 Delta variant and 56 original SARS-CoV-2 infected patients from Hunan, China, matched according to age and gender divided into two groups and compared the baseline characteristics and laboratory findings with appropriate statistical methods. Results Patients infected with the Delta variant had significantly fewer symptoms of fever (p < 0.001), fatigue (p = 0.004), anorexia (p < 0.001), shortness of breath (p = 0.004), diarrhea (p = 0.006), positive pneumonia rate of chest CT (p = 0.019) and chest CT ground glass opacities (p = 0.004) than those of patients with the original SARS-CoV-2. Patients of the Delta variant group had a significantly longer virus shedding time [41.5 (31.5, 46.75) vs. 18.5 (13, 25.75), p < 0.001] compared with the original SARS-CoV-2 group. The correlation analyses between the virus shedding time and clinical or laboratory parameters showed that the virus shedding time was positively related to the viral strain, serum creatinine and creatine kinase isoenzyme, while negatively correlated with lymphocyte count, total bilirubin and low-density lipoprotein. Finally, the viral strain and lymphocyte count were thought of as the independent risk factors of the virus shedding time demonstrated by multiple linear regression. Conclusion COVID-19 patients infected with the Delta variant exhibited fewer gastrointestinal symptoms and prolonged virus shedding time than those infected with the original SARS-CoV-2. Delta variant and fewer lymphocyte were correlated with prolonged virus shedding time.